The 'puzzles' methodology: En route to indirect inference? - Vo Phuong Mai Le; Patrick Minford; Michael Wickens (Cardiff University, Cardiff Business School, 2009)
We review the methods used in many papers to evaluate DSGE models by comparing their simulated moments with data moments. We compare these with the method of Indirect Inference to which they are closely related. We illustrate the comparison with contrasting assessments of a two-country model in two recent papers. We conclude that Indirect Inference is the proper end point of the puzzles methodology.
Keywords: C12; C32; C52; E1; 330; bootstrap; US-EU model; DSGE; VAR; indirect inference; Wald statistic; anomaly; puzzle; Bootstrap-Verfahren; Dynamisches Gleichgewicht; VAR-Modell